Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, Dan Dana Alokasi Khusus Terhadap Pengalokasian Anggaran Belanja Modal(Studi Pada Pemerintah Kabupaten/Kota di Jawa Tengah Tahun 2011-2013 - Putri, Kuntami Suryani; , Dra. Mujiyati M.Si (2016)
This study aimed to test on the influence Economic growth, local revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) towards capital expenditure budget allocation. The sample used in this study were 35 districts / cities in Central Java taken from reports on the realization revenue and expenditure budget (APBD) and Gross Regionsl Domestic Product (PDRB) at constan price from 2010 until 2013. The analytical tool used in this study is the linear regression with t-test, f-test, and test the coefficient of determination. The results of this study indicate that economic growth and the General Allocation Fund (DAU) and Special Allocation Fund (DAK) has a significant effect on capital spending. Meanwhile, local revenue (PAD) no significant effect on Capital Expenditure. Simultaneously Economic Growth, revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) has significant effect on Capital Expenditure. Key Words: Economy Growth, Local Revenue (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK), and Capital Expenditure.